The Hellenistic Ideal of the King: Text and Translation on the Neo-Pythagorean Treatise On the Kingship attributed to Diotogeno (Circe de clásicos y modernos, 2025)
Thanks to Stobaeus’ Anthologium, a significant corpus of fragments from ancient intellectual production has survived through time and reached us. Among the testimonies collected in this compilation, there exists a substantial amount of material concerning political matters, which constitutes an important source, for example, for reconstructing the Hellenistic ideal of kingship. This paper presents an unpublished Spanish translation of fragments from the neo-Pythagorean treatise On Kingship, attributed to Diotogenes. Firstly, essential background information relevant to understanding the texts is introduced; secondly, the Greek text is provided according to H. Thesleff’s 1965 edition; and finally, a Spanish version of the treatise is proposed.
Keywords: justice; law; kingship; virtue; harmony